 CHAPTER 8

Relationships between funcoids and reloids

8.1. Funcoid induced by a reloid

Every reloid

f

induces a funcoid (

FCD

)

f

FCD

(Src

f

; Dst

f

) by the following

formulas (for every

X ∈

F

( Src

f

),

Y ∈

F

( Dst

f

)):

X

[(

FCD

)

f

]

Y ⇔ ∀

F

xyGR

f

:

X

FCD

F

Y

;

h

(

FCD

)

f

iX

=

l

FCD

F

X

F

xyGR

f

)

.

We should prove that (

FCD

)

f

is really a funcoid.

Proof.

We need to prove that

X

[(

FCD

)

f

]

Y ⇔ Y u h

(

FCD

)

f

iX 6

=

F

(Dst

f

)

⇔ X u

(

FCD

)

f

1

Y 6

=

F

(Src

f

)

.

The above formula is equivalent to:

F

xyGR

f

:

X

FCD

F

Y ⇔

Y u

l

FCD

F

X

F

xyGR

f

)

6

=

F

(Dst

f

)

X u

l

FCD

F

1

Y

F

xyGR

f

)

6

=

F

(Src

f

)

.

We have

Y u

d

h

FCD

F

i

X

F

xyGR

f

=

d

Yu

h

FCD

F

i

X

F

xyGR

f

.

Let’s denote

W

=

Yu

h

FCD

F

i

X

F

xyGR

f

.

F

xyGR

f

:

X

FCD

F

Y ⇔ ∀

F

xyGR

f

:

Y u

FCD

F

X 6

=

F

(Dst

f

)

F

(Dst

f

)

/

W.

We need to prove only that

F

(Dst

f

)

/

W

d

W

6

=

F

(Dst

f

)

. (The rest

follows from symmetry.)

Let’s prove that

W

is a generalized filter base. For this it’s enough to prove that

V

=

h

FCD

F

i

X

F

xyGR

f

is a generalized filter base. Let

A

,

B ∈

V

that is

A

=

FCD

P

X

,

B

=

FCD

Q

X

where

P, Q

xyGR

f

. Then for

C

=

FCD

(

P

u

Q

)

X

is true both

C ∈

V

and

C v A

,

B

. So

V

is a generalized filter base and thus

W

is a generalized

filter base.

Proposition

799

.

(

FCD

)

RLD

f

=

FCD

f

for every

Rel

-morphism

f

.

Proof.

X

(

FCD

)

RLD

f

Y ⇔ ∀

F

xyGR

RLD

f

:

X

FCD

F

Y ⇔

X

FCD

f

Y

(for every

X ∈

F

( Src

f

),

Y ∈

F

( Dst

f

)).

Theorem

800

.

X

[(

FCD

)

f

]

Y ⇔ X ×

RLD

Y 6

f

for every reloid

f

and

X ∈

F

( Src

f

),

Y ∈

F

( Dst

f

).

146